Visible Light Communication for Video ransmissions - Dr.J.Selvin Paul Peter, Venkatesh Thota, Anirudh P (International Journal of Advanced Science and Technology, 2020)
provides data transmission of audio, text, video and others by using Light-Emitting Diodes (LEDs) to transfer data depending on light illuminative properties. In this technology, LEDs are used to transfer data into the spectrum of  visible light of LEDs. This upcoming technology can be varied with that of Wi-Fi and gives advantages like increased accessible over frequency, efficiency, security, delay and much better speed. Communication is initiated by switching the  LED light on and off at a fast speed than what is seen to the normal human eye. The Radio Frequency has huge traffic and its performance is reduced. It needs a separate module. To overcome these technologies, Visible Light Communication (VLC) is a good alternative asdits large area of receiving and resistance for interfere with the electromagnetic sources. These change leads to takeover of  the bulbs which are florescent by Light Emitting Diodes (LEDs), they in turn encourages the implementation of Visible Light Communication.  Keywords: LED, transmission, communication.